Plugging material as well as preparation method and application thereof

By preparing flexible adaptive gel-type sealing materials doped with modified sepiolite, the problem of poor temperature resistance of flexible gel-type sealing agents in the prior art under high temperature environment is solved, and effective at high temperatures is achieved Block micro-cracks and pores to reduce the risk of drilling fluid loss and well wall instability.

CN119409910AActive Publication Date: 2025-02-11CHINA NAT PETROLEUM CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411544465.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing flexible gel sealing agents have poor temperature resistance in high temperature environments, making it difficult to effectively seal microcracks and pores, resulting in accidents such as drilling fluid leakage and well wall instability.

Method used

By preparing a flexible adaptive gel-based sealing material doped with modified sepiolite, a combination of alkenyl amide, alkenyl sulfonic acid, modified sepiolite and crosslinking agent is used to form an excellent anti-temperature resistance with an alkenyl resistance using a combination of alkenyl amide, alkenyl sulfonic acid, modified sepiolite and crosslinking agent. Salt properties sealing material.

Benefits of technology

The sealing material still maintains a good medium-pressure sand bed sealing effect after aging at 160°C, effectively reducing the filtration loss of drilling fluid, improving the pressure bearing capacity of the well wall, and reducing the occurrence of underground accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409910A_ABST
    Figure CN119409910A_ABST
Patent Text Reader

Abstract

The invention provides a plugging material as well as a preparation method and application thereof. The plugging material is prepared from the following raw materials: alkenyl amide, alkenyl sulfonic acid, modified sepiolite and a cross-linking agent, the cross-linking agent comprises a combination of triallylamine and divinyl benzene; the molecular structure of the modified sepiolite contains carbon-carbon double bonds. The modified sepiolite is introduced into a network framework of the plugging material to form the modified sepiolite doped plugging material, so that the temperature resistance of the plugging material can be improved, the supporting effect can be achieved through the sepiolite, and the pressure bearing capacity of a plugging layer is effectively improved; besides, triallylamine and divinyl benzene are jointly used as cross-linking agents and are matched with other preparation raw materials, so that the plugging material has excellent temperature resistance and salt tolerance, and microcracks and pores can be effectively plugged as an additive in the drilling fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil drilling fluid, and in particular relates to a plugging material and a preparation method and application thereof. Background Art

[0002] As the demand for oil and natural gas increases year by year and oil and gas exploration technology continues to improve, more and more complex well conditions are faced in mining. These complex wells have special geological conditions, and some drilling and production methods are improperly used during the drilling process, which leads to a decrease in the pressure bearing capacity of the well wall and leakage. The occurrence of leakage will delay the drilling progress, damage the oil and gas reservoir, affect the logging work, and may further cause accidents such as well wall instability, well wall collapse and blowout. In order to prevent the occurrence of leakage, the screening and development of drilling fluid treatment agents are very important, so the development of plugging materials also needs to keep pace with the times. The solid particle materials in the commonly used plugging materials are prone to plugging layer instability during the dynamic process of drilling, resulting in plugging failure. Some chemical plugging materials have poor compatibility and difficult construction processes.

[0003] Existing flexible gel plugging agents often have poor temperature resistance and are difficult to use in high temperature environments. For example, Guo Jintang et al. prepared a gel plugging agent using acrylic acid (AA) and 2-acrylamide-2-methylpropanesulfonic acid as the main polymerization monomers, diisopropylbenzene peroxide (DCP) as the initiator, and N,N-methylenebisacrylamide (MBA) as the crosslinking agent. The gel plugging agent can withstand temperatures of up to 330°C under thermogravimetric conditions (Preparation and Performance Study of Temporary Plugging Agents for High-Temperature Reservoirs [J]. Guo Jintang, et al. Journal of Tianjin University: Natural Science and Engineering Technology Edition, 2019, 52(1):6.), but it has not been used in water-based drilling fluids for evaluation; Liu Yongbing et al. prepared a plugging agent using acrylic acid and acrylamide as the main polymerization monomers and sodium bentonite as an inorganic additive (P(AA-AM) / MMT pre-crosslinked gel particle profile control technology [J]. Liu Yongbing, et al. Geological Science and Technology Information, 2005, 24(2):4.), the plugging agent can achieve 90% effective plugging, but it can only withstand temperatures of 110°C; Xu Zhe et al. developed a new type of soft-outer-hard-inner plugging agent, which uses acrylamide and 2-acrylamide-2-methylpropanesulfonic acid as the main polymerization monomers, calcium carbonate as an inorganic additive, N,N-methylenebisacrylamide as a cross-linking agent, and ammonium persulfate-sodium bisulfite redox system as an initiator to prepare a soft-outer-hard-inner core-shell structure plugging particle with calcium carbonate as the core and polymer as the shell (Development of a new type of soft-outer-hard-inner plugging agent [J]. Xu Zhe, et al. Drilling Fluids and Completion Fluids, 2020, 037(006):726-730.), which has good plugging performance, but low temperature resistance, only 120°C.

[0004] Compared with hard solid particle plugging agents, flexible adaptive plugging agents can effectively match lost pores or cracks and are not easily washed away by drilling fluid. However, research by Li Wei et al. pointed out that the temperature resistance of most such plugging materials does not exceed 135°C (Research and Application Status of Drilling Fluid Plugging Materials and Plugging Technology Countermeasures [J]. Li Wei, et al. Science, Technology and Engineering, 2021, 21(12): 11.). Therefore, it is urgent to design a flexible adaptive plugging material with excellent temperature resistance. Summary of the invention

[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a plugging material and a preparation method and application thereof. Through the screening and design of the raw materials, the plugging material has excellent temperature and salt resistance, and can effectively plug microcracks and pores as an additive in drilling fluid.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a plugging material, wherein the raw materials for preparing the plugging material include a combination of alkenyl amide, alkenyl sulfonic acid, modified sepiolite and a cross-linking agent; the cross-linking agent includes a combination of triallylamine and divinylbenzene; and the molecular structure of the modified sepiolite contains a carbon-carbon double bond.

[0008] The plugging material provided by the present invention belongs to a kind of flexible adaptive gel plugging material, and its raw material source is wide and the cost is low; the present invention introduces modified sepiolite into the network skeleton of the plugging material to form a plugging material doped with modified sepiolite, which can not only improve the temperature resistance of the plugging material, but also play a supporting role through the sepiolite, effectively improving the pressure bearing capacity of the plugging layer. In the present invention, since triallylamine has a branched structure, the thermal stability of the three-dimensional spatial network structure of the cross-linked plugging material is higher, and divinylbenzene has a higher thermal stability itself due to the presence of benzene rings, which can further improve the thermal stability of the plugging material. The present invention uses triallylamine and divinylbenzene as cross-linking agents together, and through mutual cooperation with other raw materials for preparation, the plugging material has excellent temperature and salt resistance, and can effectively plug microcracks and pores as an additive in the drilling fluid.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0010] As a preferred technical solution, the alkenyl amide includes N-isopropylacrylamide.

[0011] Preferably, the olefin sulfonic acid comprises 2-acrylamide-2-methylpropane sulfonic acid.

[0012] Preferably, the mass ratio of the alkenyl amide to the alkenyl sulfonic acid is (2.5-9):1, for example, it can be 2.6:1, 2.8:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 8.8:1, etc.

[0013] Preferably, the raw materials for preparing the modified sepiolite include a combination of a silane coupling agent containing a carbon-carbon double bond and sepiolite.

[0014] Preferably, the mass ratio of the silane coupling agent containing carbon-carbon double bonds to sepiolite is (0.3-3):1, for example, it can be 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, etc.

[0015] Preferably, the silane coupling agent containing a carbon-carbon double bond includes γ-methacryloxypropyltrimethoxysilane and / or vinyltriethoxysilane.

[0016] Preferably, the particle size of the sepiolite is 100-200 mesh.

[0017] Preferably, the sepiolite is purified sepiolite.

[0018] Preferably, the purification method comprises:

[0019] The acid solution and the sepiolite are stirred and mixed, and then first dried to obtain the purified sepiolite.

[0020] Preferably, the acid solution comprises hydrochloric acid solution and / or sulfuric acid solution.

[0021] Preferably, the concentration of the acid solution is 0.2-2 mol / L, for example, it can be 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, etc.

[0022] Preferably, based on the mass of the sepiolite being 1 g, the volume of the acid solution is 5-25 mL, for example, 6 mL, 8 mL, 10 mL, 12 mL, 14 mL, 16 mL, 18 mL, 20 mL, 22 mL, 24 mL, etc.

[0023] Preferably, the stirring and mixing time is 10-24 h, for example, it can be 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, etc.

[0024] Preferably, the stirring and mixing temperature is 75-85°C, for example, it can be 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, etc.

[0025] Preferably, the first drying temperature is -53 to -20°C, for example, -50°C, -45°C, -40°C, -35°C, -30°C, -25°C, etc.

[0026] Preferably, the first drying time is 24-48 h, for example, it can be 26 h, 28 h, 30 h, 32 h, 34 h, 36 h, 38 h, 40 h, 42 h, 44 h, 46 h, etc.

[0027] Preferably, the preparation method of the modified sepiolite comprises:

[0028] The silane coupling agent containing a carbon-carbon double bond undergoes a second reaction with the sepiolite to obtain the modified sepiolite.

[0029] Preferably, the second reaction is carried out in the presence of an organic solvent.

[0030] Preferably, the organic solvent comprises anhydrous ethanol and / or acetone.

[0031] Preferably, the mass ratio of the organic solvent to the silane coupling agent containing carbon-carbon double bonds is 100:(1-5), for example, it can be 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, etc.

[0032] Preferably, the preparation method of the modified sepiolite specifically comprises:

[0033] The organic solvent is mixed with the silane coupling agent containing a carbon-carbon double bond, and after adjusting the pH value to 4-6, the sepiolite is added to carry out a second reaction to obtain the modified sepiolite.

[0034] The pH value is adjusted to 4-6, for example, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, etc.

[0035] Preferably, the pH value is adjusted to 4-6 by an organic acid, and the organic acid comprises acetic acid and / or oxalic acid.

[0036] Preferably, the time of the second reaction is 4-6 h, for example, it can be 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, etc.

[0037] Preferably, the temperature of the second reaction is 85-95°C, for example, it can be 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, etc.

[0038] Preferably, after the second reaction is completed, the steps of washing and second drying are also performed in sequence.

[0039] Preferably, the second drying temperature is -40 to -20°C, for example, -38°C, -36°C, -34°C, -32°C, -30°C, -28°C, -26°C, -24°C, -22°C, etc.

[0040] Preferably, the second drying time is 1-24 h, for example, it can be 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, etc.

[0041] Preferably, based on the total mass of the alkenyl amide and the alkenyl sulfonic acid as 100%, the mass of the modified sepiolite is 5-20%, for example, it can be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, etc.

[0042] Preferably, based on the total mass of the alkenyl amide and the alkenyl sulfonic acid as 100%, the mass of the crosslinking agent is 1-2%, for example, it can be 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, etc.

[0043] Preferably, the mass ratio of triallylamine to divinylbenzene is (0.5-2):1, for example, it can be 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, etc.

[0044] Preferably, the raw materials for preparing the plugging material also include a modified sepiolite carrier agent.

[0045] Preferably, the modified sepiolite carrier comprises dodecylphenol polyoxyethylene ether and / or sorbitan fatty acid ester.

[0046] Preferably, the mass ratio of the modified sepiolite to the modified sepiolite carrier is (1-5):1, for example, it can be 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, etc.

[0047] Preferably, the raw materials for preparing the plugging material also include water.

[0048] Preferably, the mass percentage of water in the raw materials for preparing the plugging material is 60-90%, for example, it can be 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, etc.

[0049] Preferably, the raw materials for preparing the plugging material also include an initiator.

[0050] Preferably, the initiator comprises a persulfate.

[0051] Preferably, the persulfate comprises ammonium persulfate and / or potassium persulfate.

[0052] Preferably, based on the total mass of the alkenyl amide and the alkenyl sulfonic acid as 100%, the mass of the initiator is 0.1-1%, for example, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, etc.

[0053] Preferably, the particle size of the plugging material is 100-200 mesh, for example, it can be 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh, etc.

[0054] In a second aspect, the present invention provides a method for preparing the plugging material according to the first aspect, the preparation method comprising:

[0055] The alkenyl amide, alkenyl sulfonic acid, modified sepiolite and a cross-linking agent are subjected to a first reaction to obtain the plugging material; the plugging material obtained by the preparation method of the plugging material provided by the present invention has high purity.

[0056] Preferably, the first reaction is carried out in the presence of water; the plugging material provided by the present invention can be obtained by aqueous solution polymerization.

[0057] Preferably, the first reaction is carried out in the presence of an initiator.

[0058] Preferably, the method for preparing the plugging material specifically comprises the following steps:

[0059] (1) mixing the alkenyl amide, the alkenyl sulfonic acid and water, and adjusting the pH value to 6-8 to obtain a solution A;

[0060] (2) mixing the modified sepiolite, water and the solution A to obtain a solution B;

[0061] (3) The solution B, the aqueous solution of the crosslinking agent and the aqueous solution of the initiator are mixed and then subjected to a first reaction to obtain the plugging material.

[0062] Preferably, the pH value in step (1) is adjusted to 6-8, for example, it can be 6.2, 6.4, 6.8, 7, 7.2, 7.4, 7.6, 7.8, etc.

[0063] Preferably, the pH value is adjusted to 6-8 in step (1) by using an alkaline substance.

[0064] Preferably, the alkaline substance comprises sodium hydroxide and / or potassium hydroxide.

[0065] Preferably, the mixed materials in step (2) also include a modified sepiolite carrier.

[0066] Preferably, the mixing time in step (2) is 20-120 min, for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, etc.

[0067] Preferably, the temperature of the first reaction is 55-60°C, for example, it can be 55.5°C, 56°C, 56.5°C, 57°C, 57.5°C, 58°C, 58.5°C, 59°C, 59.5°C, etc.

[0068] Preferably, the time of the first reaction is 3-6 h, for example, it can be 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, etc.

[0069] Preferably, after the first reaction is completed, a third drying step is further included.

[0070] Preferably, the temperature of the third drying is 60-90°C, for example, it can be 62°C, 64°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, etc.

[0071] Preferably, the third drying time is 1-24 h, for example, it can be 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, etc.

[0072] In a third aspect, the present invention provides a drilling fluid, wherein the drilling fluid comprises the plugging material as described in the first aspect.

[0073] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0074] Compared with the prior art, the present invention has the following beneficial effects:

[0075] (1) The present invention introduces modified sepiolite into the network skeleton of the plugging material through chemical bonds to form a plugging material doped with modified sepiolite, thereby improving the temperature resistance of the plugging material. At the same time, the addition of sepiolite can play a supporting role and effectively improve the pressure bearing capacity of the plugging layer;

[0076] (2) The plugging material provided by the present invention still has a good medium-pressure sand bed plugging effect after aging at 160° C. in a water-based drilling fluid, can effectively plug microcracks and pores, and reduce the filtration loss of drilling fluid. For a 80-120 mesh sand bed, the immersion degree before aging is 18.8-25.5%, and the minimum immersion degree after aging is 21.2%;

[0077] (3) The plugging material provided by the present invention can be used as an additive for drilling fluid and used in the field of plugging while drilling to reduce the leakage and filtration of drilling fluid to the well wall and reduce the occurrence of downhole accidents. The drilling fluid using the plugging material provided by the present invention has a filtration loss of 7.9-8.6 mL before aging and a filtration loss of 9.8-19.8 mL after aging at 160°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 is an infrared spectra of the sepiolite, purified sepiolite, modified sepiolite, and γ-methacryloxypropyltrimethoxysilane in Preparation Example 1;

[0079] Figure 2 It is a non-permeate loss instrument;

[0080] Figure 3 This is a morphology diagram of the plugging material provided in Example 1 after aging in a 15wt% NaCl solution at 195°C for 16h;

[0081] Figure 4 This is a morphology diagram of the plugging material provided in Example 2 after aging in a 15wt% NaCl solution at 195°C for 16h;

[0082] Figure 5 This is a morphology diagram of the plugging material provided in Example 3 after aging in a 15wt% NaCl solution at 195°C for 16h;

[0083] Figure 6 This is a morphology diagram of the plugging material provided in Example 4 after aging in a 15wt% NaCl solution at 195°C for 16 hours. DETAILED DESCRIPTION

[0084] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0085] The sources of some components in the following examples and comparative examples are as follows:

[0086] (1) Dodecylphenol polyoxyethylene ether: purchased from Adamas, Titan Technology.

[0087] Preparation Example 1

[0088] A modified sepiolite and a preparation method thereof, the preparation method comprising the following steps:

[0089] (1) 20 g of 200-mesh sepiolite was poured into 300 mL of 2 mol / L hydrochloric acid and mixed with mechanical stirring at 80° C. for 12 h, then washed with deionized water for 3 times, and freeze-dried for 48 h to obtain purified sepiolite;

[0090] (2) 50 mL of anhydrous ethanol and 1 mL of γ-methacryloxypropyltrimethoxysilane were mixed in a 100 mL beaker, and the pH value was adjusted to 4.5 with acetic acid to obtain a mixed solution;

[0091] (3) adding 2 g of the purified sepiolite to the mixed solution, refluxing at 95° C. for 4 h, washing with ethanol three times and then with water after the reaction, centrifugally freeze-drying for 24 h to obtain the modified sepiolite;

[0092] The above sepiolite, purified sepiolite, modified sepiolite and γ-methacryloxypropyltrimethoxysilane were analyzed by Fourier transform infrared analyzer (Thermo Scientific, Nicolet 6700). The test results are as follows: Figure 1 As shown by Figure 1 It can be seen that the infrared characteristic peaks of the modified sepiolite indicate that γ-methacryloxypropyltrimethoxysilane is successfully grafted onto the sepiolite.

[0093] Example 1

[0094] A plugging material, wherein the raw materials for preparing the plugging material include 9g N-isopropylacrylamide, 1g 2-acrylamide-2-methylpropanesulfonic acid, 2g modified sepiolite provided in Preparation Example 1, 100mg triallylamine, 100mg divinylbenzene, 0.5g dodecylphenol polyoxyethylene ether, 60mg ammonium persulfate and water;

[0095] The preparation method of the plugging material comprises the following steps:

[0096] (1) 9 g of N-isopropylacrylamide and 1 g of 2-acrylamide-2-methylpropanesulfonic acid were added to a 250 mL beaker, and 50 mL of deionized water was added and stirred until they were completely dissolved to obtain a monomer solution; 0.193 g of sodium hydroxide was dissolved in 20 mL of deionized water, and the pH value of the monomer solution was adjusted to 7 using the obtained sodium hydroxide solution to obtain a solution A;

[0097] (2) dissolving 2 g of modified sepiolite and 0.5 g of dodecylphenol polyoxyethylene ether in 20 mL of deionized water, and adding the resultant to the solution A after ultrasonic vibration for 20 min to obtain a solution B;

[0098] (3) 100 mg of triallylamine and 100 mg of divinylbenzene were dissolved in 20 mL of deionized water, added to the solution B, stirred for 20 min, heated in a 55° C. water bath, and slowly added with 10 mL of an aqueous solution of ammonium persulfate (containing 60 mg of ammonium persulfate); after adding the initiator, the reaction vessel was sealed, reacted for 4 h, and the product was vacuum dried at 75° C. for 24 h to obtain the plugging material.

[0099] Example 2

[0100] A plugging material and a preparation method thereof, which differs from Example 1 in that the total mass of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid remains unchanged, the mass ratio of the two is 6:1, the amount of modified sepiolite added is 1.3 g, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0101] Example 3

[0102] A plugging material and a preparation method thereof, which differs from Example 1 in that the total mass of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid remains unchanged, the mass ratio of the two is 2.5:1, the amount of modified sepiolite added is 0.5 g, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0103] Example 4

[0104] A plugging material and a preparation method thereof, which differs from Example 1 in that the total mass of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid remains unchanged, the mass ratio of the two is 2:1, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0105] Example 5

[0106] A plugging material and a preparation method thereof, which differs from Example 1 in that the total mass of N-isopropylacrylamide and 2-acrylamide-2-methylpropanesulfonic acid remains unchanged, the mass ratio of the two is 9.5:1, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0107] Example 6

[0108] A plugging material and a preparation method thereof, which differs from Example 1 only in that the amount of modified sepiolite used is 2.5 g, and the remaining raw materials, proportions and steps are the same as those in Example 1.

[0109] Example 7

[0110] A plugging material and a preparation method thereof, which differs from Example 1 only in that an equal amount of N-isopropylacrylamide is replaced by acrylamide, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0111] Comparative Example 1

[0112] A plugging material and a preparation method thereof, the preparation method comprising the following steps:

[0113] (1) 9 g of N-isopropylacrylamide and 1 g of 2-acrylamide-2-methylpropanesulfonic acid were added to a 250 mL beaker, and 50 mL of deionized water was added, and the mixture was stirred until the mixture was completely dissolved to obtain a monomer solution; 0.193 g of sodium hydroxide was dissolved in 20 mL of deionized water, and the pH value of the monomer solution was adjusted to 7 using the obtained sodium hydroxide solution to obtain a solution A;

[0114] (2) 100 mg of triallylamine and 100 mg of divinylbenzene were dissolved in 20 mL of deionized water, added to the solution A, and stirred for 20 min to obtain solution B; the solution B was heated in a 55° C. water bath, and 10 mL of an aqueous solution of ammonium persulfate (containing 60 mg of ammonium persulfate) was slowly added; after adding the initiator, the reaction vessel was sealed, reacted for 4 h, and the product was vacuum dried at 75° C. for 24 h to obtain the plugging material.

[0115] Comparative Example 2

[0116] A plugging material and a preparation method thereof, which differs from Example 1 only in that in step (3), only 200 mg of triallylamine is used as a cross-linking agent, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0117] Comparative Example 3

[0118] A plugging material and a preparation method thereof, which differs from Example 1 only in that in step (3), only 200 mg of divinylbenzene is used as a cross-linking agent, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0119] Comparative Example 4

[0120] A plugging material and a preparation method thereof, which differs from Example 1 only in that in step (3), only 200 mg of N,N-methylenebisacrylamide is used as a cross-linking agent, and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0121] Comparative Example 5

[0122] A plugging material and a preparation method thereof, which differs from Example 1 only in that no cross-linking agent is used in step (3), and the remaining raw materials, amounts and steps are the same as those in Example 1.

[0123] Performance Testing

[0124] (1) Static permeability filtration and rheological test:

[0125] 16 g of bentonite was added to 400 mL of deionized water, and then 800 mg of Na2CO3 was added, and the mixture was stirred for 20 min to obtain a 4 wt% bentonite-based slurry; the plugging materials provided in the above embodiments and comparative examples were crushed with a crusher, and the plugging materials with a size of less than 200 mesh were sieved out, and 4 g of the plugging materials with a size of less than 200 mesh were added to the 4 wt% bentonite-based slurry to obtain a drilling fluid containing the plugging materials;

[0126] According to GB / T 16783.1-2014, the drilling fluid containing plugging materials was tested using an API medium-pressure filter loss tester (Qingdao Haitongda, ZNS-5A). The working pressure was set to 0.69 MPa, the working time was 7.5 min, and the filtrate volume (FL API ) to reflect the static permeability loss resistance of the plugging material;

[0127] A six-speed rotational viscometer (Qingdao Tongchun, ZNN-D6) was used to measure the values ​​at 600 rpm and 300 rpm. The apparent viscosity (AV) and dynamic shear force (YP) were tested according to GB / T 16783.1-2014 to reflect the effect of plugging materials on the rheology of drilling fluids.

[0128] After the drilling fluid containing the plugging material was aged at 160° C. for 16 hours, the apparent viscosity, dynamic shear force and medium pressure filtration loss of the drilling fluid were tested according to the above method. The results are shown in Table 1 below:

[0129] Table 1

[0130]

[0131]

[0132] It can be seen from the test data in Table 1 that the plugging material provided by the present invention has a good effect of resisting permeability loss, and still has a good plugging effect after aging at 160°C. At the same time, the plugging material provided by the present invention has little effect on the rheological properties of the drilling fluid before and after aging; the plugging materials provided in Examples 4-7 partially decompose or completely decompose after aging, resulting in a rapid decrease in the apparent viscosity of the drilling fluid after aging, and an increase in the medium-pressure filtration loss. The plugging materials provided in Comparative Examples 1-4 are decomposed due to their heat resistance, which leads to a significant decrease in the apparent viscosity of the drilling fluid after aging, and a corresponding increase in the medium-pressure filtration loss. The plugging material provided in Comparative Example 5 does not use a cross-linking agent, has a strong hydration ability, is equivalent to a thickener, and will increase the apparent viscosity of the drilling fluid, but the filtration loss increases significantly after high-temperature aging, and has poor temperature resistance.

[0133] (2) Crack resistance filtration test:

[0134] 12 g of bentonite was added to 400 mL of deionized water, and then 600 mg of Na2CO3 was added, and the mixture was stirred for 20 min to obtain a 3 wt% bentonite-based slurry; the plugging materials provided in the above embodiments and comparative examples were crushed with a crusher and plugging materials with a size of 100-200 mesh were screened out; 4 g of the screened plugging materials were added to the 3 wt% bentonite-based slurry to obtain a drilling fluid containing the plugging materials;

[0135] Use non-permeability loss meter to simulate fracture loss in the formation. Figure 2 As shown, Figure 2 The glass device in the middle upper part is a sand-filled tube with a size of 100×500mm. A layer of filter screen is placed at the outlet below the sand-filled tube, and a layer of filter paper is placed above the filter screen to prevent quartz sand from leaking out of the outlet of the sand-filled tube. During the experiment, the penetration of the drilling fluid can be observed through the cup. Figure 2 The measuring cylinder is in the lower middle part, with a measuring range of 100mL. The valve on the right is connected to the gas cylinder, which can adjust the gas source pressure. The crack resistance filtration loss is tested as follows:

[0136] Fill the sand filling tube with 260g of quartz sand (80-120 mesh), compact the quartz sand and flatten it to 180cm 3 At the scale, slowly pour 250mL of drilling fluid containing plugging material into the sand filling tube to conduct plugging experiment; test at 0.69MPa for 7.5min, record the degree of water immersion in the sand bed (the immersion degree is expressed by the wetting ratio of the dry sand mass of the sand bed before and after the experiment, that is, the immersion degree = the mass of the wetted quartz sand / the mass of the total quartz sand × 100%), which can reflect the anti-fracture filtration performance of the plugging material;

[0137] After the drilling fluid containing the plugging material was aged at 160° C. for 16 hours, the degree of water penetration of the sand bed was tested according to the above method. The results are shown in Table 2 below:

[0138] Table 2

[0139]

[0140]

[0141] It can be seen from the test data in Table 2 that the plugging materials provided in Examples 1-3 have good crack-resistance filtration loss capability and still have good plugging effect after aging at 160°C. Before aging, the plugging materials provided in Examples 4-7 have good crack-resistance filtration loss capability. After aging at 160°C, the plugging effect of the drilling fluid containing the plugging materials provided in Examples 4-7 is significantly deteriorated or even all the drilling fluid is lost. Before aging, the drilling fluid containing the plugging materials provided in Comparative Examples 1-5 has poor crack-resistance filtration loss capability. After aging, when the sand bed is immersed in water to 100%, all the drilling fluid is lost after 30s, and the plugging effect is significantly deteriorated.

[0142] (3) Aging test:

[0143] 50g of 100-mesh plugging material was placed in a hydrothermal autoclave, 15wt% NaCl solution was added, and the material was aged at 195°C for 16h under normal pressure. After the aging, the plugging material was taken out and the morphology was observed. The results are shown in Table 3 below:

[0144] Table 3

[0145]

[0146]

[0147] It can be seen from the test data in Table 3 that the plugging material provided in Example 1 has good temperature resistance and salt resistance in a 15wt% NaCl solution, and can still maintain structural integrity and certain flexibility after aging at 195°C; the plugging materials provided in Examples 4-7 decompose to a greater extent or completely decompose, while the plugging materials provided in Comparative Examples 1-5 decompose completely. Figure 4-6 It can be seen that the plugging materials provided in Examples 2-4 become darker in color after aging. This is because the plugging materials undergo local carbonization or charring to form carbon black or brown products, and high temperature accelerates the breakage and degradation of polymer chains, which may generate some colored decomposition products, thereby darkening the color of the plugging materials.

[0148] In summary, the plugging material provided by the present invention is grafted with sepiolite to form a modified sepiolite-doped plugging material, which can effectively plug microcracks and pores, reduce water loss in drilling fluid, and can be used in an environment of 160°C. In a 15wt% NaCl solution, the structure can remain intact after aging at 195°C, and has better resistance to temperature and salt.

[0149] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the plugging material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A plugging material, characterized in that: The raw materials for preparing the plugging material include a combination of alkenyl amide, alkenyl sulfonic acid, modified sepiolite and a cross-linking agent; The cross-linking agent includes a combination of triallylamine and divinylbenzene; The modified sepiolite contains carbon-carbon double bonds in its molecular structure.

2. The plugging material according to claim 1, characterized in that: The alkenyl amides include N-isopropylacrylamide.

3. The plugging material according to claim 1 or 2, characterized in that: The alkenyl sulfonic acid includes 2-acrylamide-2-methylpropane sulfonic acid; Preferably, the mass ratio of the alkenyl amide to the alkenyl sulfonic acid is (2.5-9):

1.

4. The plugging material according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the modified sepiolite include a combination of a silane coupling agent containing a carbon-carbon double bond and sepiolite; Preferably, the mass ratio of the silane coupling agent containing a carbon-carbon double bond to sepiolite is (0.3-3):1; Preferably, the silane coupling agent containing a carbon-carbon double bond includes γ-methacryloxypropyltrimethoxysilane and / or vinyltriethoxysilane; Preferably, the sepiolite is purified sepiolite; Preferably, based on the total mass of the alkenyl amide and the alkenyl sulfonic acid being 100%, the mass of the modified sepiolite is 5-20%.

5. The plugging material according to any one of claims 1 to 4, characterized in that: The mass of the cross-linking agent is 1-2% based on the total mass of the alkenyl amide and the alkenyl sulfonic acid as 100%; Preferably, the mass ratio of triallylamine to divinylbenzene is (0.5-2):

1.

6. The plugging material according to any one of claims 1 to 5, characterized in that: The raw materials for preparing the plugging material also include a modified sepiolite carrier agent; Preferably, the modified sepiolite carrier comprises dodecylphenol polyoxyethylene ether and / or sorbitan fatty acid ester; Preferably, the mass ratio of the modified sepiolite to the modified sepiolite carrier is (1-5):1; Preferably, the raw materials for preparing the plugging material also include water; Preferably, the raw materials for preparing the plugging material further include an initiator; Preferably, the initiator comprises a persulfate; Preferably, the mass of the initiator is 0.1-1% based on the total mass of the alkenyl amide and the alkenyl sulfonic acid as 100%; Preferably, the particle size of the plugging material is 100-200 mesh.

7. A method for preparing the plugging material according to any one of claims 1 to 6, characterized in that: The preparation method comprises: The alkenyl amide, alkenyl sulfonic acid, modified sepiolite and a cross-linking agent undergo a first reaction to obtain the plugging material.

8. The preparation method according to claim 7, characterized in that: The first reaction is carried out in the presence of water; Preferably, the first reaction is carried out in the presence of an initiator; Preferably, the preparation method specifically comprises the following steps: (1) mixing the alkenyl amide, the alkenyl sulfonic acid and water, and adjusting the pH value to 6-8 to obtain a solution A; (2) mixing the modified sepiolite, water and the solution A to obtain a solution B; (3) The solution B, the aqueous solution of the crosslinking agent and the aqueous solution of the initiator are mixed and then subjected to a first reaction to obtain the plugging material.

9. The preparation method according to claim 8, characterized in that: The mixed materials in step (2) also include a modified sepiolite carrier; Preferably, the temperature of the first reaction is 55-60°C; Preferably, the first reaction time is 3-6 hours.

10. A drilling fluid, characterized in that: The drilling fluid comprises the plugging material as described in any one of claims 1-6.

Citation Information

Patent Citations

  • Oil-based drilling fluid plugging agent and preparation method thereof

    CN115247052A

  • Copolymer type filtrate reducer as well as preparation method and application thereof

    CN117820572A

  • Environment-friendly high-temperature resistant water-based drilling fluid plugging Anti-sloughing agent, preparation method thereof and the water-based drilling fluid

    US20210189216A1